Wearable Technology for Monitoring Respiratory Rate and SpO2 of COVID-19 Patients - Takahashi, Shizuko; Nakazawa, Eisuke; Ichinohe, Sakurako; Akabayashi, Aru; Akabayashi, Akira (Research Developments in Medicine and Medical Science Vol. 3, 2023)
This review explored the indicators of COVID-19 surveillance, such as vitals, respiratory condition, temperature, oxygen saturation (SpO2), and activity levels using wearable devices. With a significant number of sudden home deaths reported worldwide due to coronavirus disease 2019 (COVID-19), wearable technology has emerged as a method for monitoring this infection. This systematic review used PubMed as the database, with the keywords “COVID-19”, “Diagnosis”, and “Wearable Devices”. The search was limited to studies published between 31 December 2019, and 8 July 2022, as the pandemic occurred during this period. All types of articles with the keywords “COVID-19”, “Diagnosis”, and “Wearable Devices” were screened. Four reviewers independently screened the articles against the eligibility criteria and extracted the data using a data charting form. A total of 56 articles were on monitoring, of which 28 included SpO2 as a parameter. Although wearable devices are effective in the continuous monitoring of COVID-19 patients, further research on actual patients is necessary to determine the efficiency and effectiveness of wearable technology before policymakers can mandate its use. Although research on the effects of remote patient monitoring with pulse oximetry and respiratory rate on health outcomes is lacking, wearable devices have the potential to save hospital resources for patients who might benefit most from care escalation.